Holographic teaching presence: participant experiences of interactive synchronous seminars delivered via holographic videoconferencing - Nai Li; David Lefevre (Association for Learning Technology, 2020)
This study seeks to identify potential advantages of using holographic videoconferencing to deliver seminars within higher education as compared to the use of alternative non-holographic videoconferencing. Holographic videoconferencing offers opportunities to enhance attendees' experience of remotely delivered seminars but has not been widely researched. Data were collected from 127 attendees attending one of three seminars, each of which featured a combination of physically present presenters and remote presenters participating via holographic videoconferencing. In this study, the holographic representations were three-dimensional and life-size. Monitors and holographic images were calibrated in a manner such that the remote presenters were able to point to and achieve eye-contact with members of the audience. Results indicate that the use of holographic videoconferencing can enhance the teaching presence of remote presenters, the engagement between participants and attendees' enjoyment of a seminar. Almost all participants reported this to be their first experience of a holographic event and the positive results are partly explained by a sense of novelty. This suggests that the benefits of holographic videoconferencing may reduce over time. However, we argue that some benefit, resulting from an enhanced degree of teaching presence, will be sustained. The relative impact on learning gain is not explored in the current study. We believe that this would likely require a more controlled experiment in future research.